Governança corporativa e desempenho superior e persistente das empresas listadas na BM&FBOVESPA - Caldas, Álvaro José Ribeiro (2015)
The theme corporate governance covers several aspects of the organization, as well as its relationships with stakeholders, considering approaches that relate to the maximization of shareholder returns and, increasingly, with the vision of oriented shareholder who understands the need for meet the satisfaction of multiple legitimate interests, internal and external to the organization for inclusion in the company's objectives and its strategies and legal provisions. Corporate governance on the one hand, generates agency costs to align and monitor the activities manager, denounced by the agency theory, and, on the other hand, favors the mitigation of transaction costs in the contracts, listed by the theory of transaction costs. In this context, corporate governance considers the actors relationship systems with conflicting interests and the mechanisms that control decision-making in organizations. This research aimed to analyze the relationship between corporate governance and the upper and persistent performance of publicly traded company listed on the Stock Exchange, Commodities and Futures (BM&FBOVESPA). It is presented as a descriptive, quantitative and document strategy. It was used an index that represents the adoption of good corporate governance practices adapted literature (LEAL; CARVALHAL-DA-SILVA, 2007; LAMEIRA, 2007; SILVEIRA et al., 2009; IBGC, 2009; LAMEIRA et al., 2010; LAMEIRA, 2012), with the highlight of care to the orientation of multiple interests and corporate responsibility perspective for sustainable business performance. Companies selected for inclusion in the population were listed on BM & FBOVESPA, active, issuing common shares on the date of 08.28.2014, which showed the variable market value for the period 2010-2013 in Economática® base, excluded the performance of companies in the sector “Financial and Other”, composing, after examination of documents examined, a final population of 221 companies. As for the results, it was observed that companies with superior performance and persistent in market value perspective have their distinct governance practices of companies that did not have competitive advantage, confirming one of the hypotheses of the specific objectives. Moreover, the financial metric, one can see an association between classes of IGC and persistent upper and financial performance. It can be observed that the IGC level of the analyzed companies is correlated to higher performance, to characterize advantage in financial performance and, more strongly, the market value in relation to competitors in the business sector, according to the classification of BM&FBOVESPA, which favors greater reputation evidenced by transparency, contribute to further reduction of agency conflicts. However, considering the correlation between IGC and higher and persistent performance for the entire survey period, significance was not found, rejecting thus hypotheses related to the general objective of the research. This may be given under this association represents a sustainable advantage, both in financial terms and in market value only in relation to industry rivals in which it operates, but that is not necessarily related to advantage in relation to other listed companies. So if that can favor the advantage of a company is to have a high IGC in a sector; in other sectors, companies may not need a level of corporate governance disclosure as high for obtaining advantage in recorded performance relative to their competitors